Association Between CD4/CD8 Ratio Recovery and Chronic Kidney Disease Among Human Immunodeficiency Virus-Infected Patients Receiving Antiretroviral Therapy: A 17-Year Observational Cohort Study - Qin, Fengxiang; Lv, Qing; Hong, Wen; Wei, Di; Huang, Kui; Lan, Ke; Chen, Rongfeng; Liu, Jie; Liang, Bingyu; Liang, Huayue; Liang, Hao; Qin, Shanfang; et al. (Frontiers in Microbiology, 2022)
Background: CD4/CD8 ratio is considered as an emerging biomarker for HIV-related diseases. However, the relationship of CD4/CD8 ratio recovery and chronic kidney disease (CKD), and whether cumulative antiretroviral therapy (ART) is effective in the CD4/CD8 ratio recovery and in reducing CKD incidence among HIV patients remain unclear. Methods: A 17-year observational cohort study was conducted on all HIV-infected patients receiving ART in Guangxi, China. Kaplan–Meier analysis was used to investigate the cumulative CKD incidence. Cox regression and propensity score matching (PSM) were used to evaluate the association between CD4/CD8 ratio recovery and CKD incidence, and the effect of ART regimens on CD4/CD8 ratio recovery and CKD incidence. Results: A total of 59,268 eligible individuals contributing 285,143 person-years of follow-up, with an overall CKD incidence of 10.69%. After ART, patients who developed CKD showed higher mortality than those with normal kidney function (12.48% vs. 7.57%, p<0.001). Patients whose CD4/CD8 ratio did not recover to 0.7 had a higher CKD incidence than the patients who recovered (aHR= 2.84, 95% CI 2.63–3.07), similar to the PSM analysis (aHR=3.13, 95% CI 2.85–3.45).Compared with the PI-based and INSTI-based regimens, NNRTI-based regimen had a better CD4/CD8 ratio recovery rate (27.04%, 16.16% and 29.66%, respectively) and a lower CKD incidence (17.43%, 16.16%, and 7.31% respectively). Conclusions: This large-scale real-world setting provide new evidence that the CD4/CD8 ratio recovery is associated with lower CKD incidence in HIV-infected patients receiving ART. NNRTI-based is a better choice for CD4/CD8 ratio recovery and reducing the risk of CKD.